3D Meniscus‐Guided Evaporative Assembly for Rapid Template‐Free Synthesis of Highly Crystalline Perovskite Nanowire Arrays. (7th August 2022) - Kim, Seongchan; Jo, Sae Byeok; Yun, Tae Keun; Lee, Sol; Kim, Kwanpyo; Choi, Young Jin; Kang, Joohoon; Cho, Jeong Ho
Abstract: Low‐dimensional nanostructures of halide perovskites have been receiving extensive research interest for their superior optical, electrical, and stability characteristics over their conventional bulk counterparts. In particular, the unique surficial characteristics of well‐defined 1D nanowires have shown high feasibility for high performance optoelectronic applications. The key aspect of endorsing this nanoscale form factor in practical applications lies in securing dimensional uniformity and controllability in large scales, which generally requires complicated lithographic procedures. In this work, a simple, rapid, and widely applicable strategy for the direct synthesis and printing of well‐aligned nanowire arrays on a large scale is demonstrated. By employing blade coating methods with sophisticatedly controlled stick‐slip motions, periodically resolved transverse 3D meniscus enables uniform directional growth of highly crystalline CsPbI3 nanowires without the need for templates. A systematic investigation of morphological evolutions with respect to kinetic processing variables is conducted, along with a comprehensive suite of structural and optical analyses for the synthesized nanowire arrays. A single nanowire photodetector is employed to demonstrate the superiority and applicability of the fabrication strategy. Finally, a 2D image recognition is demonstrated by using an array of photodetectors fabricated via a fast (<2 min) direct printing of nanowire arrays on wafers. Abstract : A 6 × 6 array of photodetectors based on compact and well‐aligned nanowire arrays is developed using a simple 3D‐meniscus‐guided evaporative assembly strategy coupled with stick‐slip motion‐controlled blade coating. The introduction of modified stick‐slip motion can induce stable and regular transverse perturbations of 3D meniscus between the colloidal solution of precursors and the substrate.